Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2196/24156
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Acceptability of a Smartphone App Intervention (ChildSafe) in Malaysia: Qualitative Exploratory Study

Abstract: Background Home is a vulnerable place for accidental child injuries. Unintentional injuries are a leading cause of death, hospitalization, and disabilities. These injuries are considered preventable and if not tackled, they will continue to be a persisting problem. Smartphones have become increasingly important in our everyday life and is an important tool not only for communication but also for other purposes—they have apps that can be used for various purposes. Therefore, an app-based interventio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Usability is not just about the presentation of knowledge but also deals with ergonomic design, user-friendly settings, and accessibility (eg, clear layout, icons and their comprehensibility, and understandable error messages [ 61 ]) as well as technical setting options. Although some of the studies (2/5, 40%) evaluated aspects such as the layout of the apps, icon selection, and comprehensibility, they did not use a comprehensive concept of software ergonomics [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usability is not just about the presentation of knowledge but also deals with ergonomic design, user-friendly settings, and accessibility (eg, clear layout, icons and their comprehensibility, and understandable error messages [ 61 ]) as well as technical setting options. Although some of the studies (2/5, 40%) evaluated aspects such as the layout of the apps, icon selection, and comprehensibility, they did not use a comprehensive concept of software ergonomics [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some unintentional injuries in our study showed more significant reductions in the PPS analysis. This suggests that watching an educational video on paternal involvement in childcare not just once, but several times, may increase the effectiveness of the programme, and improving accessibility may have a longer-lasting effect on unintentional injury prevention 39…”
Section: Discussionmentioning
confidence: 99%
“…23 Apps downloadable on smartphones were convenient and effective yet was found to lack interactive features. 24 Interventions using a mix of traditional face-to-face and social media were well received by parents 25 and adoelscents. 26 Engagement, however, was noted to be higher using social media due to its convenience 25 affordability and privacy.…”
Section: Introductionmentioning
confidence: 99%